Analysis of the Pronunciation of Iqra' in QS. Al-'Alaq Verse 1 through the Rules of Insya' Talab Amr and Its Implications in Islamic Da'wah Methods - Nurin Alfiani Nurin; Muhammad Arwani Rofi’i; Fuji Lestari (Maddah: Journal of Advanced Da'wah Management Research, 2025)
The word iqra' in QS. Al-'Alaq verse 1 is one of the words that is interesting to study. Why the word iqra' became the first revelation revealed to the Prophet Muhammad SAW, who was ummi, and the ambiguity of the object that must be read, raises profound questions about the hidden meaning in that word. This study aims to reveal the deeper meaning of the word iqra' through the kaidah insya' talab amr in the science of ma'ani Al-Qur'an, and its implications in Islamic da'wah methods. This study uses the library research method with an approach based on the science of ma'ani Al-Qur'an. The results of the study show that the rule of insya' talab amr requires the implementation of a task by a higher party to a lower party. The phrase iqra' in the Qur'an is mentioned 16 times in 8 surahs with different derivations, which shows the importance of this command in various contexts. The word iqra' (read) is a form of fiil amr which, in the study of ma'ani science, is included in the insya' talab rule, which demands that something be done. In addition to the literal meaning of "read," the word iqra' has multiple meanings, including commands to study, collect, convey, examine, recite, explore thoroughly, and compile. The results of the study show that the command iqra' not only encouraged the Prophet Muhammad SAW to read in the literal sense, but also to understand, practice, and spread knowledge. This reflects the importance of knowledge, education, and the dissemination of information as fundamental elements in Islamic preaching, which emphasizes that the methods of Islamic preaching must be rooted in education and the comprehensive dissemination of knowledge, in accordance with the command iqra' which became the basis of the Prophet Muhammad SAW's preaching.